Bridging D–A type photosensitizers with the azo group to boost intersystem crossing for efficient photodynamic therapy. Issue 14 (23rd March 2022) - Hao, Boyi; Wang, Jiaxin; Wang, Chao; Xue, Ke; Xiao, Minghui; Lv, Shuyi; Zhu, Chunlei
Abstract : A novel and effective strategy is developed for enhanced photosensitization by bridging D–A type photosensitizers with the azo group, holding great potential in high-quality photodynamic therapy with rapid prediction of the therapeutic outcome. Abstract : Photodynamic therapy (PDT) has attracted much attention in disease treatments. However, the exploration of a novel method for the construction of outstanding photosensitizers (PSs) with stimuli-responsiveness remains challenging. In this study, we, for the first time, report a novel and effective strategy to boost reactive oxygen species (ROS) generation by bridging donor–acceptor (D–A) type PSs with the azo group. In contrast to the counterpart without azo-bridging, the azo-bridged PSs exhibit remarkably enhanced ROS generation via both type-I and type-II photochemical reactions. Theoretical calculations suggest that azo-bridging leads to a prominent reduction in Δ E ST, thereby enabling enhanced ROS generation via efficient intersystem crossing (ISC). The resulting azo-bridged PS (denoted as Azo-TPA-Th(+)) exhibits a particularly strong bactericidal effect against clinically relevant drug-resistant bacteria, with the killing efficiency up to 99.999999% upon white light irradiation. Since azo-bridging generates an azobenzene structure, Azo-TPA-Th(+) can undergo trans -to- cis isomerization upon UV irradiation to form emissive aggregates by shutting down the ISC channel. By virtue of the fluorescence turn-on property of unbound Azo-TPA-Th(+), we propose a straightforward method to directly discern the effective photodynamic bactericidal dose without performing the tedious plate-counting assay. This study opens a brand-new avenue for the design of advanced PSs with both strong ROS generation and stimuli-responsiveness, holding great potential in high-quality PDT with rapid prediction of the therapeutic outcome.